Validation of the Spanish version of the Pain Catastrophizing Scale for Children (PCS-C) - Guillermo Ceniza-Bordallo; Andrés Gómez Fraile; Patricia Martín-Casas; Ibai López- (Elsevier, 2023)
Introduction: Pain catastrophizing is a powerful factor that can affect health care outcomes as well as emotional and physical well-being. The Pain Catastrophizing Scale for Children (PCS-C) is widely used, but it is not validated in Spanish. The aim of the study was to translate the PCS-C to Spanish and assess the validity and reliability of the translated version. Patients and methods: This study was carried out in two phases: (a) instrument translation (via a translation-back-translation process) and (b) psychometric analysis (construct validity: exploratory and confirmatory factor analysis, internal consistency, floor and ceiling effects and convergent validity). It had a cross-sectional design and was conducted on a sample of children aged 8-18 years was selected by convenience in a paediatric hospital. The study followed the STARD checklist. Results: The sample included 150 children and adolescents (mean age, 12.45 years; 63.8% male) and their parents. The exploratory and the confirmatory analysis showed a good adjustment of the model to the original 3-model structure with 13 items. The internal consistency of the scale was excellent (Cronbach α, 0.904), and no floor or ceiling effects were detected. In the convergent validity analysis, the Spanish version of the PCS-C showed a moderate correlation with pain interference (r = 0.400) and with health-related quality of life (r = 0.217-0.303). Conclusions: These results show that the Spanish version of the PCS-C is a valid and reliable scale to assess pain catastrophizing in children and adolescents. Resumen: Introducción: El catastrofismo relacionado con el dolor es un factor influyente en el pronóstico del tratamiento, así como en el bienestar emocional y físico. La escala pediátrica Pain Catastrophizing Scale for Children (PCS-C) es ampliamente utilizada, pero no está validada en español. Este estudio tuvo como objetivo traducir la PCS-C al español y evaluar su validez y fiabilidad. Pacientes y métodos: Este estudio se llevó a cabo en dos fases: a) traducción del instrumento (mediante un proceso de traducción directa e inversa) y b) análisis psicométrico (validez de constructo: análisis factorial exploratorio y confirmatorio, consistencia interna, efectos suelo y techo, y validez convergente) a través de un estudio transversal con una muestra seleccionada por conveniencia, de un hospital pediátrico compuesta por niños de 8 a 18 años. Este estudio siguió la lista de verificación STARD. Resultados: En el estudio se incluyó a 150 niños y adolescentes (edad media = 12,45; 63,8% varones) y sus padres. El análisis exploratorio y posteriormente el análisis confirmatorio mostraron un buen ajuste del modelo a la estructura original de tres modelos con 13 ítems. La consistencia interna de la escala resultó excelente (α de Cronbach = 0,904) y no se detectaron efectos techo ni suelo. En cuanto al análisis de validez convergente, la PCS-C en español mostró una correlación moderada con la interferencia del dolor (r = 0,400) y con la calidad de vida relacionada con la salud (r = 0,217-0,303). Conclusiones: Estos resultados demuestran que la versión en español de la PCS-C es una escala válida y fiable para evaluar el catastrofismo relacionado con el dolor en niños y adolescentes.